(untitled) (Research, Society and Development, 2025)
Women’s health in primary education is essential for female students’ well-being and development. Traditionally, general activities on this topic caused discomfort due to derogatory comments. To improve effectiveness, specific interventions were introduced. The objective of this study was to provide scientific. Knowledge about women’s health to female students in Elementary School II. The activities included: i) a school presentation; ii) a survey of prior knowledge; and iii) educational interventions. Results showed that 52% of students knew about endometriosis, 80% used contraceptives, and 80% were followed by gynecologists. While these numbers indicate preventive measures, they also reveal gaps in reproductive physiology knowledge, likely due to limited scientific information access. The findings highlight schools as key spaces for disseminating health information. Outreach projects help undergraduate students share knowledge and contribute to public health. The experience gained will support future initiatives to strengthen health education in primary schools.